Perbandingan Perkembangan Bahasa Anak Usia 0-3 Tahun Di Panti Asuhan Dan Keluarga - Widyastuti, Nurvita, dr. Rusmawita, M.Kes.,Sp.A (2016)
Background: Language is a form of oral communication, writing and gestures which symbolize. Language development is an overall indicator of the child's cognitive ability, which language delays can be detected early. Language delay can be influenced by the function in the everyday life of the child. Objective: To determine the ratio of language development of children aged 0-3 years in orphanages and family. Methods: The method used in this peneliian analytic observational with cross sectional study design. The subjects were all children in the Child Care Foundation and Toys (YPAB) and child health centers in some work areas Ngoresan Posyandu, Jebres, Surakarta. Sample collection using sampling saturated (census) with a sample of 22 children. Measuring instruments used in this study is the CAT and clams. Data analysis using unpaired t test using SPSS 22.0 for windows. Results: From the data obtained result in an orphanage FSDQ average 58.9% and the average family FSDQ at 109.3% with p <0.001 while the mean difference -50.39% FSDQ (IK95% = -34.4% to -66.3%). Conclusions: There are differences in the language development of children in orphanages and in families.